2020
DOI: 10.2298/botserb2002219k
|View full text |Cite
|
Sign up to set email alerts
|

Jumping the barrier: Does a glacier tongue affect species distribution along the elevation gradient in the subnival and nival belts? A case study on Mt. Kazbegi, Georgia, Central Great Caucasus Mountains

Abstract: Glaciers are a prominent feature in high mountains and can affect plant distribution along the gradients. However, the possible effect of glaciers on plant community structure at landscape scale has been little studied. We asked: if a glacier tongue crosses a slope laterally and potentially blocks dispersal and migrations, how can this affect vegetation structure and species composition below and above this barrier? A suitable study system is offered by slopes on Mt. Kazbegi, where we establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…), slope angle (inclination), slope aspect, soil pH, plant available N, P, K, AMMT, SOM (%), vegetation projective cover (%) and plant community data (plant species and their frequency of occurrence). In our previous work we found that vegetation cover was reducing exponentially with increasing elevation (Kikvidze et al, 2020), and for statistical analyses we logtransformed cover data assuming a linear dependence of log-transformed cover on elevation. We used correlation analysis and multivariate ordination methods such as non-Metric Multidimensional Scaling (NMDS; Legendre, Gallagher, 2001), Principal Component Analysis (PCA; Mason, Gunst, 1985), and Canonical Correspondence Analysis (CCA; Palmer, 1993).…”
Section: Data Analysesmentioning
confidence: 99%
“…), slope angle (inclination), slope aspect, soil pH, plant available N, P, K, AMMT, SOM (%), vegetation projective cover (%) and plant community data (plant species and their frequency of occurrence). In our previous work we found that vegetation cover was reducing exponentially with increasing elevation (Kikvidze et al, 2020), and for statistical analyses we logtransformed cover data assuming a linear dependence of log-transformed cover on elevation. We used correlation analysis and multivariate ordination methods such as non-Metric Multidimensional Scaling (NMDS; Legendre, Gallagher, 2001), Principal Component Analysis (PCA; Mason, Gunst, 1985), and Canonical Correspondence Analysis (CCA; Palmer, 1993).…”
Section: Data Analysesmentioning
confidence: 99%